An improved GC-MS-SIM analytical method for determination of pendimethalin residue in commercial crops (leaf and soils) and its validation - Anindita Paul; Sujan Majumder; L. K. Prasad; M. Sheshu Madhav; Nalli Johnson; K. Padmaja; Satyapriya Singh (PLoS ONE, 2025)
Pendimethalin is generally used as pre-emergence herbicide cum suckericide in different growing region of Flue-Cured Verginia (FCV) tobacco by applying indiscriminately in irrigation channel. In quest of safety regulations related to pendimethalin residues in cured leaf tobacco and tobacco growing soils, a rapid and robust method is developed by GC-MS single quadruple system.. The GC-MS single ion monitoring (SIM) analytical method, achieved good linearity (R2 > 0.99) with LOD and LOQ values of 0.001 mg/kg and 0.005 mg/kg, respectively. The method gave more than 80% recovery (5% RSD) showed compliance with international specification of DG-SANTE guidelines. In the majority of samples, pesticide residue levels were below the guidance residue levels (GRL; for pendimethalin GRL 5 ppm) value set by Center for Scientific Research Relative to Tobacco (CORESTA). The analytical method developed for true detection of pendimethalin residue at very trace levels with acceptable recovery level and matrix effect. The method is improved in terms of sentivity and precision as per regulatory norms of exporting commercial crops like tobacco. Looking at the consumer safety the method can be used in monitoring the pendimethalin residues in FCV tobacco and FCV tobacco grown soils at regular intervals.